Interpretation and Views of Quranic Commentaries on Peace Based on Al-SalÄm and Al-Amn Terms - Adenan, Faezy; Rahman, Asmak Ab (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2020)
Peace is a very important topic for discussion in a world of war, chaos and insecurity. Islam is a religion that prioritises peace and rejects all forms of violence. The term “peace” is repeated often in the Qur’an, in phrases such as al-salām and al-amn, with meanings of peace, security and harmony. This study seeks to identify phrases in the Qur’an relating to peace and to present the views of quranic commentaries (mufasirin) regarding these phrases. The methodology applied in this study is based on data compiled from library research by using deductive and analysis methods. The study shows that among the terminologies used in reference to the meaning of peace are al-salām and al-amn which have been certified by the Quranic commentaries in their books. Indirectly, through Quranic verses it shows that element of peace is one of the messages brought by Islam.